Morfologia radular e descrição da estrutura populacional e reprodutiva do molusco gastrópode Hastula cinerea (BORN, 1778) (CONOIDEA: TEREBRIDAE) - Luz, Índira Oliveira da (2021)
Gastropod molluscs of the superfamily Conoidea are marine predators that occur in tropical and subtropical regions of the planet. They have variable radular morphology, such as the hypodermic radular tooth, harpoon-shaped and with the presence of a venom gland, characterizing it as a toxoglossa radula. The Terebridae family is part of this group of toxoglossas and among its diverse number of species is Hastula cinerea (Born, 1778). The species H. cinerea inhabits a sandy region beach and feeds mainly on polychaetes. It is a gonochoric species and has internal fertilization, with larval development with intracapsular metamorphosis. This thesis was structured in two chapters. In Chapter 1, we tested the hypotheses that there is variation between the radular teeth of males and females of H. cinerea and that there is a relationship between the size of the radular tooth and the size of the individual's shell in the study population. In Chapter 2, we tested the hypotheses that the population has a heterogeneous population size structure in the region under study; the sex ratio is 1:1; and the population of the semi-arid region of NE Brazil has continuous reproduction with spawning peaks during the dry period. Samples were collected on the sandy beach of Flecheiras, in the municipality of Trairi, west coast of Ceará, NE Brazil. After the radular morphology was analysed using Scanning Electron Microscopy (SEM), the hypothesis of radular sexual dimorphism was refuted. However, radular variation was found in the population, with structural and size differences, which confirms the hypothesis of a relationship between the size of the radular tooth and the size of the individual's shell. To analyse the population and reproductive structure, monthly collections were carried out during the period from June 2017 to August 2018 in the wave swept zone of Flecheiras beach, Trairi, Ceará. Salinity was verified during collections and rainfall data were obtained from the Fundação Cearense de Meteorologia e Recursos Hídricos (FUNCEME). For the observation of histological characteristics, standard protocols of applied basic histology were used. Together with analysis of abiotic data, the following results were obtained: the population size structure of H. cinerea was heterogeneous with individuals ranging from 10.49 mm to 49.48 mm; the sex ratio of the species in the region does not follow the pattern of 1:1, having a larger number of females; and the reproductive cycle is continuous, but the hypothesis of the occurrence of spawning peaks only in the dry period was refuted. These results contribute to research on the knowledge of the radular functional morphology of the species H. cinerea and also add information to the knowledge about the reproductive biology of the species, thus contributing to the database of toxoglossa radula molluscs from tropical regions.